Ariadne-1. A vital Drosophila gene is required in development and defines a new conserved family of ring-finger proteins. - Aguilera, M.; Oliveros, M.; Martinez-Padron, M.; Barbas, J.A.; Ferrus, A. (Genetics, 2000)
We report the identification and functional characterization of ariadne-1 (ari-1), a novel and vital Drosophila gene required for the correct differentiation of most cell types in the adult organism. Also, we identify a sequence-related gene, ari-2, and the corresponding mouse and human homologues of both genes. All these sequences define a new protein family by the Acid-rich, RING finger, B-box, RING finger, coiled-coil (ARBRCC) motif string. In Drosophila, ari-1 is expressed throughout development in all tissues. The mutant phenotypes are most noticeable in cells that undergo a large and rapid membrane deposition, such as rewiring neurons during metamorphosis, large tubular muscles during adult myogenesis, and photoreceptors. Occasional survivors of null alleles exhibit reduced life span, motor impairments, and short and thin bristles. Single substitutions at key cysteines in each RING finger cause lethality with no survivors and a drastic reduction of rough endoplasmic reticulum that can be observed in the photoreceptors of mosaic eyes. In yeast two-hybrid assays, the protein ARI-1 interacts with a novel ubiquitin-conjugating enzyme, UbcD10, whose sequence is also reported here. The N-terminal RING-finger motif is necessary and sufficient to mediate this interaction. Mouse and fly homologues of both ARI proteins and the Ubc can substitute for each other in the yeast two-hybrid assay, indicating that ARI represents a conserved novel mechanism in development. In addition to ARI homologues, the RBR signature is also found in the Parkinson-disease-related protein Parkin adjacent to an ubiquitin-like domain, suggesting that the study of this mechanism could be relevant for human pathology.